Constitutional change and democracy in Indonesia - Horowitz, Donald L. (Cambridge, [England] Cambridge University Press, 2013)
"This is the story of how democracy became entrenched in the world's largest Muslim-majority country. After the fall of its authoritarian regime in 1998, Indonesia pursued an unusual course of democratization. It was insider-dominated and gradualist, and it involved free elections before a lengthy process of constitutional reform. At the end of the process, Indonesia,ãWs amended constitution was essentially a new and thoroughly democratic document. By proceeding as they did, the Indonesians averted the conflict that would have arisen between adherents of the old constitution and proponents of radical, immediate reform. Gradual reform also made possible the adoption of institutions that preserved pluralism and pushed politics toward the center. The resulting democracy has a number of prominent flaws, largely attributable to the process chosen, but is a better outcome than the most likely alternatives. Donald L. Horowitz documents the decisions that gave rise to this distinctive constitutional process. He then traces the effects of the new institutions on Indonesian politics and discusses their shortcomings as well as their achievements in steering Indonesia away from the dangers of polarization and violence, all the while placing the Indonesian story in the context of comparative experience with constitutional design and intergroup conflict".
1. A distinctive path -- 2. Democratization before renovation -- 3. Creeping reform: reconfiguring the political infrastructure -- 4. A game of inches -- 5. Anomalies, ironies, regularities, and surprises -- 6. The shape of the new system -- 7. Low-quality democracy and its discontents -- 8. Causes, consequence, and the consequences of consequences.
Includes bibliographical references and index.
Keywords: Democratization -- Indonesia -- History; Democracy -- Indonesia; Constitutional history -- Indonesia; Indonesia -- Politics and government -- 1998-.